Deep Breathing Exercise and Active Range of Motion Influence Physiological Response of Congestive Heart Failure Patients - Nirmalasari, Novita; Mardiyono, Mardiyono; Dharmana, Edi; Arifin, Thohar (Nurse Media Journal of Nursing, 2020)
Background: Dyspnea and physiological changes are clinical manifestations of Congestive Heart Failure (CHF) due to respiratory failure. Deep breathing exercise combined with active range of motion increases respiratory muscles and blood circulation. As a result, it reduces breathing effort and decreases blood pressure.Purpose: This research aimed to analyze the influence of deep breathing exercise and active range of motion (ROM) on physiological response of CHF patients.Methods: This study used a quasi-experiment with pretest-posttest control group design recruiting 32 respondents by stratified random sampling technique. The intervention was done three times a day for three days. Deep breathing exercise for thirty times and continued with active range of motion for five times each movement was given. Digital sphygmomanometer and digital watch were used as measuring instruments. Data were analyzed using independent and paired t-tests.Result: The results showed that there were significant differences in the systole (p=0.000), diastole (p=0.000) and respiratory rates (p=0.003) after the intervention compared to the control group. There was also a significant difference in systolic blood pressure between the intervention and the control group (p=0.003). However, no significant difference in diastole and respiratory rates was found.Conclusion: Deep breathing exercise combined with active range of motion decreases the systole in CHF patients. Further research is expected to lengthen the time of intervention to allow better significance.